PENGARUH MODAL INTELEKTUAL TERHADAP PROFITABILITAS DAN PRODUKTIVITAS PERUSAHAAN DALAM INDEX LQ45 - Putri, Yuni Murdiana; Kurnia, Kurnia (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
Intellectual capital is a concept in assessing financial performance that is quite developed in recentyears. However,there are some companies which have not reported of intangible assets in the form of intellectualcapital, particularly the human capital which has contribution in the making of competitive advantage inwinning the tight competition. The purpose of this research is to test the influence of intellectual capital to theprofitability and the productivity of the company. The population is all companies which are incorporated in theLQ45 index in the 2010-2014 periods. The samples have been selected by using purposive sampling technique so17 companies in the LQ45 which meets the criteria have been selected. The analysis technique has been done byusing the simple regressions analysis. The result of the test shows that the intellectual capital does not have anyinfluence to the profitability of the company. It occurs because of the magnitude of the intellectual capital whichis measured by using the burden of the employees does not becomethe assurance of the magnitude of theperformance of the employees, so the burden of the employees will increase, but the net profit does not show anysignificant changes. Meanwhile, the intellectual capital has positive influence to the productivity. It means thatthe enhancement of the intellectual capital gives benefit to the company and it becomes the potential element inincreasing the productivity of the company.Keywords: Intellectual Capital, Profitability, Productivity.